Operational Definitions Related to Pediatric Ventilator Liberation - Abu-Sultaneh, Samer; Iyer, Narayan Prabhu; Fernández, Analía; Gaies, Michael; González-Dambrauskas, Sebastián; Hotz, Justin Christian; Kneyber, Martin C.J.; López-Fernández, Yolanda M.; Rotta, Alexandre T.; Werho, David K.; Baranwal, Arun Kumar; Blackwood, Bronagh; et al. (Elsevier, 2023)
Background: Common, operational definitions are crucial to assess interventions and outcomes related to pediatric mechanical ventilation. These definitions can reduce unnecessary variability among research and quality improvement efforts, to ensure findings are generalizable, and can be pooled to establish best practices. Research Question: Can we establish operational definitions for key elements related to pediatric ventilator liberation using a combination of detailed literature review and consensus-based approaches? Study Design and Methods: A panel of 26 international experts in pediatric ventilator liberation, two methodologists, and two librarians conducted systematic reviews on eight topic areas related to pediatric ventilator liberation. Through a series of virtual meetings, we established draft definitions that were voted upon using an anonymous web-based process. Definitions were revised by incorporating extracted data gathered during the systematic review and discussed in another consensus meeting. A second round of voting was conducted to confirm the final definitions. Results: In eight topic areas identified by the experts, 16 preliminary definitions were established. Based on initial discussion and the first round of voting, modifications were suggested for 11 of the 16 definitions. There was significant variability in how these items were defined in the literature reviewed. The final round of voting achieved ≥ 80% agreement for all 16 definitions in the following areas: what constitutes respiratory support (invasive mechanical ventilation and noninvasive respiratory support), liberation and failed attempts to liberate from invasive mechanical ventilation, liberation from respiratory support, duration of noninvasive respiratory support, total duration of invasive mechanical ventilation, spontaneous breathing trials, extubation readiness testing, 28 ventilator-free days, and planned vs rescue use of post-extubation noninvasive respiratory support. Interpretation: We propose that these consensus-based definitions for elements of pediatric ventilator liberation, informed by evidence, be used for future quality improvement initiatives and research studies to improve generalizability and facilitate comparison.
Keywords: airway extubation; extubation failure; high-flow nasal cannula; mechanical ventilation; noninvasive ventilation; pediatric ICU; ventilator weaning